Male and Female PPG Students’ Use of KeLIP in an ESL Course - Kamariah, Yunus; Wahidah, Abd Wahid; Sharifah Nor Madiah, Syed Omar (2015)
Gender difference has been acknowledged as one of the several factors impacting learner success in the use of Information and Communication Technology (ICT). This study purported to examine gender differences in the use of KeLiP (KUSZA e-Learning Programme) among PPG (Program Pensiswazahan Guru) in UniSZA (Universiti Sultan Zainal Abidin), Malaysia. The pretest and posttest (of a similar test comprising two English components - grammar and vocabulary) was employed to examine a difference in the test scores of the male and female groups. 31 male and 120 female second batch PPG students taking UBI 3012 English course (English for Academic Communication) offered by the Faculty of Languages and Communication, UniSZA participated in this study. An independent samples t-test was used to measure a difference in group scores. There was no significant difference found between the two group scores in the posttest, indicating that gender factor does not significantly influence the use of KeLiP among the PPG students in UniSZA. Future research to examine the impact of this factor in the use of ICT in classroom may reveal different results.